Cross-cultural adaptation and psychometric properties of an Arabic language version of the Brief Illness Perception Questionnaire in Lebanon. Issue 1 (1st January 2016) - Saarti, Stéphanie; Jabbour, Hicham; Osta, Nada El; Hajj, Aline; Khabbaz, Lydia Rabbaa
Abstract : Background: Patients' positive illness perceptions (IPs) significantly contribute to treatment success. The Brief Illness Perception Questionnaire (Brief IPQ) is widely used in various diseases for assessing IPs. It was developed in English-speaking countries and studies on it in Arab countries are scarce. Objectives, Setting and design: This observational cross-sectional study aimed to cross-culturally adapt the Brief IPQ English version into a modern Arabic language version and determine its psychometric properties in a sample of Lebanese cardiac disease patients. This study was approved by the Institutional Review Board of Saint Joseph University of Beirut, Lebanon. Participants: A convenience sample of 30 patients with cardiac disease were recruited during routine visits to cardiologists' offices in Beirut, Lebanon. Inclusion criteria were at least one cardiac disease for at least 6 months with no acute episode or exacerbation of the disease during the 6 preceding months, age≥18 years, and the ability to read and comprehend Arabic. The pre-final version of the Brief IPQ Arabic version was tested for face and content validity. The meaning, comprehensibility, and acceptability were studied by individual interviews. For discriminant validity and internal consistency of the Brief IPQ Arabic version (Brief IPQ-Ar), 100 patients were recruited in a similar manner using the same inclusion criteria. To assess reproducibility, 30 patients, selected randomly from the 100 patients, filled the questionnaire a second time, 3–4 weeks after its first administration and under the same conditions. Main outcome measures: Psychometric properties of the Brief IPQ-Ar among Lebanese patients suffering from cardiac diseases. Results: Semantic equivalence between the Brief IPQ-Ar questions and patients' descriptions was 100%. Cronbach's alpha was 0.717, which shows good internal consistency. Reproducibility was satisfactory (ICC values>0.776). Moreover, the Brief IPQ-Ar discriminated participants according to the type of cardiac disease and treatment-related characteristics. Conclusions: We confirm that the Brief IPQ-Ar is appropriate for exploring IPs in cardiac disease patients whose first language is Arabic. Further research should be conducted to test this Arabic version in other types of diseases.